Management of AF Based on New Science and New Guidelines - Vinall, Maria (MD Conference Express, 2014)
This article discusses new research on atrial fibrillation (AF) and how it may contribute to disease management, the use of novel oral anticoagulants in periprocedural anticoagulation management, the clinical overlap between AF and heart failure, as well as an overview of new ACC/AHA/HRS guideline recommendations.